Case Report: Denys–Drash Syndrome With WT1 Causative Variant Presenting as Atypical Hemolytic Uremic Syndrome - Cheng, Cheng; Chen, Lizhi; Wen, Sijia; Lin, Zhilang; Jiang, Xiaoyun (Frontiers in Pediatrics, 2020)
The WT1 variant is confirmed to be pathogenic for the Denys-Drash syndrome (DDS), a rare disorder characterized by early-onset nephrotic syndrome and renal failure, pseudo-hermaphroditism, and a high risk of Wilms’ tumor. Several cases of DDS presenting with atypical hemolytic uremic syndrome (aHUS) have been reported. Here, we report the case of a 2-year-old child who was diagnosed with WT1 missense variant, associated with DDS and initial presentation of aHUS. Complement factor H autoantibodies were negative. Complement regulatory system-related gene variants were not found, but a de novo heterozygous c.754G>A missense variant in exon 9 of WT1 gene was detected, resulting in a p. Asp252Asn substitution, by next-generation sequencing. The patient was a female morphologically but proved to be a genetic male because of the karyotype 46, XY with normally developed female external genitalia. Bilateral nephrectomy and renal transplantation were performed 1 year later, and there was no recurrence of aHUS 10 months after transplantation.